Blood type and blood donation behaviors: An empirical test of pure altruism theory - Shusaku Sasaki; Yoshifumi Funasaki; Hirofumi Kurokawa; Fumio Ohtake (Osaka University, Institute of Social and Economic Research (ISER), 2018)
We examined whether the knowledge that your private donation has a large number of potential recipients causes you to give more or less. We found that the people with blood type O are more likely to have donated blood than those with other blood types, by using a Japan's nationally representative survey. This association was found to be stronger in a subsample of individuals who knew and believed that blood type O can be medically transfused into individuals of all blood groups. However, we found that blood type O does not have any significant relationship with the other altruistic behaviors (registration for bone-marrow donation, intention to donate organs, and the making of monetary donations) and altruistic characteristics (altruism, trust, reciprocity, and cooperativeness). After further analyses, we confirmed that the wider number of potential recipients of blood type O donations promoted the blood-donation behaviors of the people with this blood type.
Keywords: I10; D64; C30; 330; ABO blood group; blood donation; group size; public good; pure altruism; behavioral economics